Economic valuation of cactus pear production in semi-arid regions of India - Louhaichi, Mounir; Hassan, Sawsan; Yigezu, Yigezu; Kumar, Sunil; Naorem, Anandkumar; Kauthale, Vitthal; Palsaniya, Dana; Patel, Sachin (2022)
Dataset about cactus pear production and economic evaluation in India. The dataset is part of a survey series, targeting farmer planting cactus across 5 countries: Tunisia, India, Jordan, Mexico and Chile.